Effects of tumor grade and dexamethasone on myeloid cells in patients with glioma. (2nd November 2018) - Moyes, Kara W; Davis, Amira; Hoglund, Virginia; Haberthur, Kristen; Lieberman, Nicole AP; Kreuser, Shannon A; Deutsch, Gail H.; Franco, Stephanie; Locke, Darren; Carleton, Michael O; Gilbertson, Debra G; Simmons, Randi; et al.
ABSTRACT: Efforts to reduce immunosuppression in the solid tumor microenvironment by blocking the recruitment or polarization of tumor associated macrophages (TAM), or myeloid derived suppressor cells (MDSCs), have gained momentum in recent years. Expanding our knowledge of the immune cell types, cytokines, or recruitment factors that are associated with high-grade disease, both within the tumor and in circulation, is critical to identifying novel targets for immunotherapy. Furthermore, a better understanding of how therapeutic regimens, such as Dexamethasone (Dex), chemotherapy, and radiation, impact these factors will facilitate the design of therapies that can be targeted to the appropriate populations and retain efficacy when administered in combination with standard of care regimens. Here we perform quantitative analysis of tissue microarrays made of samples taken from grades I-III astrocytoma and glioblastoma (GBM, grade IV astrocytoma) to evaluate infiltration of myeloid markers CD163, CD68, CD33, and S100A9. Serum, flow cytometric, and Nanostring analysis allowed us to further elucidate the impact of Dex treatment on systemic biomarkers, circulating cells, and functional markers within tumor tissue. We found that common myeloid markers were elevated in Dex-treated grade I astrocytoma and GBM compared to non-neoplastic brain tissue and grade II-III astrocytomas. Cell frequencies in these samples differed significantly from those in Dex-naïve patients in a pattern that depended on tumor grade. In contrast, observed changes in serum chemokines or circulating monocytes were independent of disease state and were due to Dex treatment alone. Furthermore, these changes seen in blood were often not reflected within the tumor tissue. Conclusions: Our findings highlight the importance of considering perioperative treatment as well as disease grade when assessing novel therapeutic targets or biomarkers of disease.